The return of great power rivalry : democracy versus autocracy from the ancient world to the U.S. and China - Kroenig, Matthew (New York, N.Y. : Oxford University Press, 2020)
"The United States of America has been the most powerful country in the world for over seventy years, but recently the U.S. National Security Strategy declared that the return of great power competition with Russia and China is the greatest threat to U.S. national security. Further, many analysts predict that America's autocratic rivals will have at least some success in disrupting-and, in the longer term, possibly even displacing-U.S. global leadership. Brilliant and engagingly written, The Return of Great Power Rivalry argues that this conventional wisdom is wrong. Drawing on an extraordinary range of historical evidence and the works of figures like Herodotus, Machiavelli, and Montesquieu and combining it with cutting-edge social science research, Matthew Kroenig advances the riveting argument that democracies tend to excel in great power rivalries. He contends that democracies actually have unique economic, diplomatic, and military advantages in long-run geopolitical competitions. He considers autocratic advantages as well, but shows that these are more than outweighed by their vulnerabilities. Kroenig then shows these arguments through the seven most important cases of democratic-versus-autocratic rivalries throughout history, from the ancient world to the Cold War. Finally, he analyzes the new era of great power rivalry among the United States, Russia, and China through the lens of the democratic advantage argument. By advancing a "hard-power" argument for democracy, Kroenig demonstrates that despite its many problems, the U.S. is better positioned to maintain a global leadership role than either Russia or China. A vitally important book for anyone concerned about the future of global geopolitics, The Return of Great Power Rivalry provides both an innovative way of thinking about power in international politics and an optimistic assessment of the future of American global leadership." --Publisher's description.
Democracy versus autocracy --The democratic advantage in history -- The democratic advantage today -- The democratic advantage in the future.
Includes bibliographical references (pages 245-260) and index.
Keywords: Balance of power; Balance of power -- History; Democracy; Democracy -- History; Authoritarianism; Authoritarianism -- History; Great powers